The Author's View of Child Parenting in the Nadham Nasihat Manuscript by Muhammad Rasyid - Aldin Alif Pratama; Yusro Edy Nugroho (Sutasoma : Jurnal Sastra Jawa, 2026)
The research was motivated by the importance of studying manuscripts as cultural heritage that convey moral educational values, especially regarding child-rearing patterns in the family. The object of the study was the Nadham Nasihat Manuscript by Muhammad Rasyid, which contains teachings or guidance on life, especially within the family sphere, written in the form of Nadham in Arabic Pegon script. An objective approach was used in this study, treating the text as a complete, autonomous work. Hermeneutic theory was used to interpret each author's intent and purpose according to Schleiermacher's hermeneutic concept, which was applied to analyze grammatical and psychological aspects and to interpret the advice in the verses of the Nadham Nasihat manuscript. The study found that the verses of advice in Nadham Nasihat reflect the author's views on child-rearing: parents must avoid being stingy and selfish, are obliged to teach manners to their children, and must marry off their children when they are old enough. This demonstrates that the verses in each piece of advice in the manuscript relate to the author's thoughts and express concern about the family's low moral order. The values in the manuscript are deemed relevant for parents in providing good parenting for their children in today's modern world.